BIOCHEMICAL INDICATORS AND APPLICATION OF Cyanobacteria Spirulina MICROALGAE IN THE CATTLE FEEDSTUFF - B. A. Khalmurzayeva; ismailkhodjaev@mail.ru; K. P. Kuatbekova; R. S. Alibekov; A. I. Makhatova; S. S. Meimanbaeva (Academic Scientific Journal of Chemistry, 2021)
The qualitative and quantitative compositions of the valuable biologically active substances, species and strains of microalgae are related the genus of Cyanobacteria Sp.platensis and Sp.labgrinthifosmis that were isolated from local nature and grown in semi-production facilities were considered. In order to adapt for mass cultivation, algae were first grown in greenhouse conditions. The algae were cultivated within 12 days. The productivity in the tubular cultivator with stirring of Sp.platensis was 3.8 g / l, protein (73.0%), and Sp.laberinthiformis was 2.6 g / l of protein (63.1%). Similar studies were carried out in the open-air conditions that showed an increase in the amount of illumination causes a significant restructuring of the entire photosynthetic apparatus of algae. The accumulation of Sp.labyrinthiformis 2.7 g / l a.d.c., protein 62.21%, and Sp.platensis 4.08 g / l, protein 75.3%, were within 10 days. The content of protein and carotenes sharply increases in comparison with the greenhouse conditions. It was found that the addition of Sp.platensis suspension, as a protein-vitamin supplement for the bulls’ feedstuff, stimulates physiological processes that improves the biochemical parameters of their blood, the digestibility coefficient of nutrients by 8-9%, positive mineral balance, increases live weight gain (17.4%) and slaughter yield of the bulls (3.6%). So, the suspension of Sp.platensis is recommended for use as a protein-vitamin supplement in livestock farms that will allow having a significant economic effect in livestock farming, in average 20-25% profits per yearly